Blue carbon, red states, and Paris Agreement Article 6 - Orford, Adam D. (Frontiers in Climate, 2024)
Coastal U.S. states, including many that have opposed proactive U.S. climate policies, are contemplating entrance into the supply side of the international carbon credit markets by, among other things, hosting revenue-generating blue carbon projects on their submerged lands. The voluntary carbon credit markets already facilitate private investment in such activities, and the emerging Paris Agreement Article 6 framework is poised to generate investment interest at the national level as well. Reviewing these trends, this Perspective questions whether this is good climate, environmental, and social policy, and advises further oversight and accountability.